THE USE OF THINK TALK WRITE STRATEGY IN TEACHING WRITING - . Totoil (The Ellite of Unira, 2021)
“Think-Talk-Write (TTW)” Strategy is a cooperative learning mode to make teaching and learning process easier. This research used the qualitative research. The target population, in this study, was the English teacher and the Eighth grade students of MTs al-Azhar Toket Proppo Pamekasan the members of population is 20 students. Data were obtained firstly from the observation sheet. , the writer also collected the data by interviewing the English teacher of the Eighth Grade. In analyzing the data, the researcher used descriptive qualitative Strategy in order to make it easier for the readers to get the description about theuse of “Think Talk Write Model” and its strengths and weaknesses.The writer analyzed the data in three basic and simple steps. Some strengths teaching writing using TTW model such as: It makes students to be independent, it makes students to be cooperative, to build a good teamwork. So, they help each other, it makes students think smarter, speak fluent and write systematically. Meanwhile the weaknesses are, When students work in ground, some of them are easy to lose their own skill and confident because they are dominated by others.